Urban and rural differences in frequency of fruit, vegetable, and soft drink consumption among 6–9‐year‐old children from 19 countries from the WHO European region. (7th July 2021) - Heinen, Mirjam M.; Bel‐Serrat, Silvia; Kelleher, Cecily C.; Buoncristiano, Marta; Spinelli, Angela; Nardone, Paola; Milanović, Sanja Musić; Rito, Ana Isabel; Bosi, A. Tülay Bağci; Gutiérrrez‐González, Enrique; Pudule, Iveta; Abdrakhmanova, Shynar; et al.
Summary: In order to address the paucity of evidence on the association between childhood eating habits and urbanization, this cross‐sectional study describes urban–rural differences in frequency of fruit, vegetable, and soft drink consumption in 123, 100 children aged 6–9 years from 19 countries participating in the fourth round (2015–2017) of the WHO European Childhood Obesity Surveillance Initiative (COSI). Children's parents/caregivers completed food‐frequency questionnaires. A multivariate multilevel logistic regression analysis was performed and revealed wide variability among countries and within macroregions for all indicators. The percentage of children attending rural schools ranged from 3% in Turkey to 70% in Turkmenistan. The prevalence of less healthy eating habits was high, with between 30–80% and 30–90% children not eating fruit or vegetables daily, respectively, and up to 45% consuming soft drinks on >3 days a week. For less than one third of the countries, children attending rural schools had higher odds (OR‐range: 1.1–2.1) for not eating fruit or vegetables daily or consuming soft drinks >3 days a week compared to children attending urban schools. For the remainder of the countries no significant associations were observed. Both population‐based interventions and policy strategies are necessary to improve access to healthy foods and increase healthy eating behaviors among children.